22nd International Conference on Advanced Information Networking and Applications - Workshops (Aina Workshops 2008) 2008
DOI: 10.1109/waina.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptable Application Offloading Scheme Based on Application Behavior

Abstract: The advancement of personal devices such as PDAs and mobile phones become ubiquitous and their increasing computing capabilities allow users to perform tasks that used to be performed on workstations. However, we cannot expect to run all tasks on top of personal devices because of the limited resources. Application Offloading allow us to overcome this issue by porting part of an application to a nearby server or workstation with more capabilities. In this paper we present a new application offloading mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Rudenko et al in [11] demonstrated by experiments that significant energy can be saved by computation offloading. Gonzalo et al in [12] developed an adaptive offloading algorithm based on both the execution history of applications and the current system conditions. Xian et al in [13] introduced an efficient timeout scheme for computation offloading to increase the energy efficiency on mobile devices.…”
Section: Related Workmentioning
confidence: 99%
“…Rudenko et al in [11] demonstrated by experiments that significant energy can be saved by computation offloading. Gonzalo et al in [12] developed an adaptive offloading algorithm based on both the execution history of applications and the current system conditions. Xian et al in [13] introduced an efficient timeout scheme for computation offloading to increase the energy efficiency on mobile devices.…”
Section: Related Workmentioning
confidence: 99%
“…This method is efficient only if all the factors are accurately known in advance. Prediction algorithms include history-based prediction [14,15], fuzzy control [16], and probabilistic prediction [17]. It involves onetime partitioning of the application, i.e., during its design time.…”
Section: Static and Dynamic Partitioningmentioning
confidence: 99%
“…A task scheduling algorithm based on the Lyapunov optimization theory was proposed in [33], which combined task offloading, device-base station association, and the optimal scheduling of sleep mode on base stations to minimize the overall energy consumption of equipment and base stations. An adaptive sequential offloading task was proposed to solve these problems in [8] that mobile users could make offloading decisions sequentially based on the current interference environment and available computing resources [34][35][36]. This could achieve good results in reducing delay and energy consumption.…”
Section: Introductionmentioning
confidence: 99%